Penerapan Pembelajaran Inovatif Melalui Projek Penguatan Profil Pelajar Pancasila Dalam Membentuk Karakter Siswa - Feni Annisa; Mila Karmelia; Siti Tiara Maulia (Departement of Mathematics Education, 2023)
The achievement of results from the learning process requires innovation at all times so that educators can rethink what strategies should be carried out in different conditions and situations. The Pancasila student profile is an effort to improve the quality of education that prioritizes character building. In an effort to build and strengthen the character of students, schools can apply the profile of Pancasila students in the current independent learning curriculum. The research method used is library research or literature study which contains theories related to this research problem. In this study the formulation of the problem is to find out